Zur Opposition restriktiv/nichtrestriktiv im Hocharabischen und im Deutschen (Journal of the College of Languages (JCL), 2018)
This paper deals with the restrictive/nonrestrictive relative clauses in German and Arabic. I will, first of all, be concerned with some theories that have been provided to define the restrictive and the nonrestrictive relative clauses, particularly with the phonetic hypothesis. It will be, then, shown that the phonetic aspect is unable to give clear answers in this respect. The best way to determine restrictivity in both languages is, I think, by implementing of semantic indicators.